HEMATOLOGICAL AND BIOCHEMICAL CHANGES IN SHEEP BLOOD FOLLOWING THE COMBINED ADMINISTRATION OF A VACCINE AGAINST CLOSTRIDIAL INFECTIONS WITH IMMUNOSTIMULANTS AND VITAMINS - Ergashev, N.B.; Mengliyev, G‘.A.; Salimov, I.X. (Research Focus International Scientific Journal, 2026)
In this study, the veterinary preparations E-Selenium and Gamavit were administered to sheep during vaccination against clostridial diseases in order to enhance the natural resistance of the organism. Blood samples were collected from experimental animals prior to vaccination and administration of the preparations, as well as on days 14, 35, and 180 after treatment. The blood samples were analyzed for erythrocyte count, leukocyte count, hemoglobin concentration, erythrocyte sedimentation rate (ESR), and biochemical parameters of blood serum. The results of the study demonstrated a statistically significant increase in erythrocytes leukocytes, and hemoglobin concentration in the blood of sheep, as well as an elevation in biochemical parameters of blood serum.